The Influence of Guided Inquiry Learning Using Flash Based Invertebramedia on the Senior High School Studentsâ Learning Achievement - Anifatussholihah, Anifatussholihah; Utami, Nur Rahayu; Subekti, Niken (Journal of Biology Education, 2018)
This research aims to know the influence of guided inquiry learning with flash based Invertebramedia on the learning outcome of senior high school students. The research was done in SMA N 1 Pamotan using Quasi Experimental Design. The sample of the study was X MIPA 1 class (experimental group) and X MIPA 2 class (control group) which was taken by purposive sampling technique. The results showed that there were increasing of cognitiveâs learning outcome of the experiment group was 80% and control group was 34.2%. There was a significant difference in the average of cognitive learning outcomes of the experimental group and control group. Analysis of affective and psychomotor aspects showed that learning outcome the experimental group higher that the control group. So, the activity of students during learning process was enchancement. The average of the studentâs questionnaire responses after joining the learning was 84.9% in good criteria. The teacher and the students also gave good responses on the implementation of the learning in general. The conclusion of the research is the application of guided inquiry learning with Invertebramedia based on flash influence on high school studentâs learning outcomes.